Assessing Empathy in Salvadoran High-Risk and Gang-Involved Adolescents and Young Adults: A Spanish Validation of the Basic Empathy Scale. (November 2013) - Salas-Wright, Christopher P.; Olate, René; Vaughn, Michael G.
Empathy is considered a key construct in the empirical study of high-risk adolescent and young adult delinquency, crime, and violence. This study examined the psychometric properties and criterion-related validity of a Spanish adaptation of the Basic Empathy Scale (BES), which is an important measure designed to capture both affective and cognitive empathy that has been validated in multiple languages but not in Spanish. The study's sample consisted of 208 high-risk and gang-involved adolescents and young adults in the Greater San Salvador Metropolitan Area. The original BES was reduced from its 20-item design to a more culturally appropriate 7-item design. The results of the confirmatory factor analysis and criterion-related validity analysis indicate that the adapted BES is a valid and reliable multidimensional measure of empathy for high-risk Salvadoran adolescents and young adults. Consistent with previous findings, females reported lower levels of empathy than males and delinquent/violent respondents reported lower levels of empathy than their nonoffender counterparts.